#Choose to challenge - the value of women (Alternate Horizons, 2024)
I choose to challenge the value of women in a South Africa based on gender roles and socialisation, leading to female inferiority and male superiority. Some South Africans display their gender roles based on cultural, societal and psychological behaviours of being a man or a woman. Keeping this in mind may help understand specific societal issues that South African women face. This essay investigates some prominent features that societal organisation has placed on gender that may lead to more significant problems if unattended.